Key Factors Shaping Customer Choices of Deposits at BSI KC Binjai: Faktor-faktor Utama yang Membentuk Pilihan Nasabah dalam Menabung di BSI KC Binjai - Dea Puspita; Rahmat Daim Harahap; Wahyu Syarvina (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: The rapid growth of Islamic banking in Indonesia, driven by increasing public awareness of sharia principles, has intensified competition in deposit services. Specific Background: Bank Syariah Indonesia (BSI) KC Binjai, operating in a highly religious region, offers sharia-compliant deposit products using a profit-sharing scheme. Knowledge Gap: Despite prior studies on Islamic banking, limited research addresses customer decision-making specifically regarding sharia deposits in the unique socio-cultural context of Binjai. Aims: This study investigates the influence of religiosity, social factors, and bank reputation on customer decisions to choose sharia deposits at BSI KC Binjai. Results: Using a quantitative descriptive method and regression analysis on data from purposive sampling, findings reveal all three variables significantly affect customer choices, with bank reputation being the most dominant (β = 0.567, p < 0.001). The model explains 78.7% of the variance in customer decisions. Novelty: This research fills a regional gap in the literature by examining deposit decisions in a localized, religiously-influenced market using robust statistical methods. Implications: The results guide BSI KC Binjai and regulators such as OJK in tailoring marketing and policy strategies that emphasize trust, social influence, and religious alignment to enhance customer engagement.HIghlight : Religiosity is the most influential factor in customer decisions to choose sharia deposits at BSI KC Binjai. Regression analysis shows 78.7% of customer decision variance is explained by religiosity, social, and reputation factors. Reputation of the bank has the strongest individual impact among the three variables studied. Keywords : Customer Decisions, Sharia Deposits, Bank Syariah Indonesia, Religiosity, Bank Reputation